PH and excipient profiles during formulation of highly concentrated biotherapeutics using bufferless media. Issue 11 (28th July 2020) - Jabra, Mario G.; Tao, Yinying; Moomaw, John F.; Yu, Zhao; Hotovec, Brian J.; Geng, Steven B.; Zydney, Andrew L.
Abstract: Several models have been developed to describe the shifts in pH and excipient concentrations seen during diafiltration of monoclonal antibody (mAb) products accounting for both Donnan equilibrium and electroneutrality constraints. However, these models have assumed that the mAb charge is either constant or only a function of pH, assumptions that will not be valid when formulating highly concentrated mAbs using bufferless or low‐buffered media due to the change in local H + concentration at the protein surface. The objective of this study was to incorporate the effects of both pH and ionic strength on the mAb charge, through the use of a charge regulation model based on the amino acid sequence of the mAb, into an appropriate mass balance model to describe the pH and excipient profiles during diafiltration. The model involves no adjustable parameters, with the protein charge evaluated directly from the protonation/deprotonation of the ionizable amino acids accounting for the electrostatic interactions between the charged mAb and the H + ions. Model predictions are in excellent agreement with experimental data for the pH and ion concentrations during diafiltration of a mAb and fusion protein with different isoelectric points and different formulation conditions. Model simulations are then used to obtain fundamental insights into the factors controlling the diafiltration behavior as well as guidelines for development of diafiltration processes to achieve target bufferless formulation conditions. Abstract : Diafiltration into bufferless solution causes significant change in protein charge due to reduction in ionic strength and shift in pH. New model including charge regulation effects based on protein amino acid sequence in excellent agreement with data for pH and excipient concentrations